Four redundant axiomatics - Cedilnik, Anton (Matrika, 2023)
In the paper, we shorten four axiom systems which are redundant in the mathematical literature.
Keywords: aksiomski sistemi; algebra with scalar involution; axiom systems; inner product spaces; metric spaces; metrični prostori; normed spaces; normirani prostori